Microwave-assisted pyrolysis in biomass and waste valorisation: Insights into the life-cycle assessment (LCA) and techno-economic analysis (TEA) - Shin Ying Foong; Yi Herng Chan; Peter Nai Yuh Yek; Serene Sow Mun Lock; Bridgid Lai Fui Chin; Chung Loong Yiin; John Chi-Wei Lan; Su Shiung Lam (Chemical Engineering Journal, 2024)

Microwave processing of oil palm wastes for bioenergy production and circular economy: Recent advancements, challenges, and future prospects - Shin Ying Foong; Yi Herng Chan; Serene Sow Mun Lock; Bridgid Lai Fui Chin; Chung Loong Yiin; Kin Wai Cheah; Adrian Chun Minh Loy; Peter Nai Yuh Yek; William Woei Fong Chong; Su Shiung Lam (Bioresource Technology, 2023)

Future feed resources in sustainable salmonid production: A review - Sissel Albrektsen; Raine Kortet; Peter Vilhelm Skov; Elisabeth Ytteborg; Susanne Gitlesen; Dorinde Kleinegris; Liv‐Torunn Mydland; Jon Øvrum Hansen; Erik‐Jan Lock; Turid Mørkøre; Philip James; Xinxin Wang; et al. (Reviews in Aquaculture, 2022)
Aquaculture is one of the most resource‐efficient and sustainable ways to produce animal protein. The Food and Agriculture Organization predicts that cultivated aquatic species will provide around 53% of the world's seafood supply by 2030. Further growth of intensive farmed aquatic species may be limited by a shortage of feed resources. The aquaculture sector therefore needs to intensify its search for alternative ingredients based on renewable natural resources. A significant increase in production will require an accelerated transition in technology and production systems, better use of natural available resources, development of high‐quality alternative feed resources and exploitation of available space. The present review discusses the urgent need to identify appropriate alternative ingredients for a sustainable future salmonid production. We describe and evaluate the most promising marine ingredients, including low‐trophic species (mesopelagic fish, zooplankton, polychaetes, macroalgae and crustaceans), novel microbial ingredients (bacteria, yeast and microalgae), insects (black soldier fly, yellow meal worm and crickets), animal by‐products (poultry meal, meat and bone meal, blood meal and hydrolysed feather meal) and by‐products from other commercial productions (trimmings and blood). Furthermore, we discuss the available volumes and need for new processing technologies and refining methods to ensure commercial production of nutritionally healthy ingredients. The essential production steps and considerations for future development of sustainable and safe seafood production are also discussed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin‑Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin-Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Isolation and characterization of bacteriophage NTR1 infectious for Nocardia transvalensis and other Nocardia species - Stephanie Taylor; Teagan L. Brown; Joseph Tucci; Peter Lock; Robert J. Seviour; Steve Petrovski (Virus Genes, 2019)

The game-changing potential of digitalization for sustainability: possibilities, perils, and pathways - Peter Seele; Irina Lock (Sustainability Science, 2017)

Theorizing stakeholders of sustainability in the digital age - Irina Lock; Peter Seele (Sustainability Science, 2017)

Integrating data-driven ecological models in an expert-based decision support system for water management in the Du river basin (Vietnam) - Thu Huong Hoang; Ans Mouton; Koen Lock; Niels De Pauw; Peter L. M. Goethals (Environmental Monitoring and Assessment, 2013)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Integrated Constructed Wetlands (ICW): Ecological Development in Constructed Wetlands for Manure Treatment - Pieter Boets; Evi Michels; Erik Meers; Koen Lock; Filip M. G. Tack; Peter L. M. Goethals (Wetlands, 2011)

Radiation Fog. Part II: Large-Eddy Simulations in Very Stable Conditions - Aurore Porson; Jeremy Price; Adrian Lock; Peter Clark (Boundary-Layer Meteorology, 2011)

Did global warming and alien invasions affect surf zone hyperbenthic communities on sandy beaches in Belgium? - Koen Lock; Jan Mees; Magda Vincx; Peter L. M. Goethals (Hydrobiologia, 2011)

Using long-term monitoring to investigate the changes in species composition in the harbour of Ghent (Belgium) - Pieter Boets; Koen Lock; Peter L. M. Goethals (Hydrobiologia, 2011)

Regional‐scale measurements of CH 4 exchange from a tall tower over a mixed temperate/boreal lowland and wetland forest - Cindy Werner; Kenneth Davis; Peter Bakwin; Chuixiang Yi; Dale Hurst; Loreen Lock (Global Change Biology, 2003)
The biosphere–atmosphere exchange of methane (CH 4 ) was estimated for a temperate/boreal lowland and wetland forest ecosystem in northern Wisconsin for 1997–1999 using the modified Bowen ratio (MBR) method. Gradients of CH 4 and CO 2 and CO 2 flux were measured on the 447‐m WLEF‐TV tower as part of the Chequamegon Ecosystem–Atmosphere Study (ChEAS). No systematic diurnal variability was observed in regional CH 4 fluxes measured using the MBR method. In all 3 years, regional CH 4 emissions reached maximum values during June–August (24±14.4 mg m −2 day −1 ), coinciding with periods of maximum soil temperatures. In 1997 and 1998, the onset in CH 4 emission was coincident with increases in ground temperatures following the melting of the snow cover. The onset of emission in 1999 lagged 100 days behind the 1997 and 1998 onsets, and was likely related to postdrought recovery of the regional water table to typical levels. The net regional emissions were 3.0, 3.1, and 2.1 g CH 4 m −2 for 1997, 1998, and 1999, respectively. Annual emissions for wetland regions within the source area (28% of the land area) were 13.2, 13.8, and 10.3 g CH 4 m −2 assuming moderate rates of oxidation of CH 4 in upland regions in 1997, 1998, and 1999, respectively. Scaling these measurements to the Chequamegon Ecosystem (CNNF) and comparing with average wetland emissions between 40°N and 50°N suggests that wetlands in the CNNF emit approximately 40% less than average wetlands at this latitude. Differences in mean monthly air temperatures did not affect the magnitude of CH 4 emissions; however, reduced precipitation and water table levels suppressed CH 4 emission during 1999, suggesting that long‐term climatic changes that reduce the water table will likely transform this landscape to a reduced source or possibly a sink for atmospheric CH 4 .

Predicting the Capillary Imbibition of Porous Rocks from Microstructure - David Benavente; Peter Lock; M Ángeles García Del Cura; Salvador Ordóñez (Transport in Porous Media, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Glutathione depletion in the liver and brain produced by 2-chloropropionic acid: relevance to cerebellar granule cell necrosis - I. Wyatt; Andrew Gyte; G. Mainwaring; Peter S. Widdowson; E. A. Lock (Archives of Toxicology, 1996)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)

Calmodulin-mediated cadmium inhibition of phosphodiesterase activity, in vitro - Gert Flik; Jan G. J. van de Winkel; Peter Pärt; Sjoerd E. Wendelaar Bonga; Robert A. C. Lock (Archives of Toxicology, 1987)